Variabilidad de la verdad según Tomás de Aquino - Darós, William Roberto (Sapientia, 2019)
The conception of the truth and its non-variability is fundamental both to understand us through a language and for social coexistence. It is analyzed then: a) both the ontological variability of the truth, and b) the possibility of the social historical variability of the truth, c) without it losing the fundamental value of truth, from the perspective of the writings of Thomas Aquinas. In general, there has been a unifying concept of truth in the history of Thomistic philosophy, which we could translate with the expression "the truth is one." An "immaculate conception" has been made of the truth, that is, a conception that did not take into account the means in which the truth is given. The concept of uniformity or univocity or identity of truth and the analogy of truth in several different minds are clarified. The truth is one - according to the thought of Thomas Aquinas - the truth is identical, if there is identity in the thing of which one has true knowledge, and if there is identity in the minds that know that thing, that is, if two or more minds have the same means and ways of knowing, whether they are metaphysically constitutive means of those minds, whether they are historically or contingently constitutive means of the same. To say that "the truth is one" is to get out of this world and of all historical circumstances: only for God is the truth only and is its own essence, the only means by which it knows everything. We mortals have diverse mentalities and admitting this fact does not necessarily lead to relativism.